2013
DOI: 10.1590/s0100-736x2013000600017
|View full text |Cite
|
Sign up to set email alerts
|

Reducing bumblefoot lesions in a group of captive Magellanic penguins (Spheniscus magellanicus) with the use of environmental enrichment

Abstract: Pesq. Vet. Bras. 33(6) Captive penguins are prone to pododermatitis (bumblefoot) lesions due to sedentary habits, changes in normal activity patterns, prolonged time on hard and abrasive surfaces, and less time swimming in the water. Environmental enrichment allows the use of creative and ingenious techniques that aim to keep the captive animals occupied by increasing the range and the diversity of behavioral opportunities always respecting the ethological needs of the species. The main goal of this work was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…The management of animals in captivity to decrease the time standing and maintain a standard of swimming similar to that observed in the wild is difficult because of the limited space that is not stimulating for birds, so measures of environmental enrichment and conditioning are recommended [19]. In this study, the routine of penguins was not changed to avoid interference with results.…”
Section: Resultsmentioning
confidence: 99%
“…The management of animals in captivity to decrease the time standing and maintain a standard of swimming similar to that observed in the wild is difficult because of the limited space that is not stimulating for birds, so measures of environmental enrichment and conditioning are recommended [19]. In this study, the routine of penguins was not changed to avoid interference with results.…”
Section: Resultsmentioning
confidence: 99%
“…In order to prevent the occurrence of bumblefoot by reducing inactivity, plenty of space was provided for the penguins to swim in the exhibit pools and through the underwater gateways that connect three sections of the Pinguin ario (Sellera et al, 2014;Nascimento et al, 2015). Studies carried out elsewhere showed that enhancing the time birds spent in the water by using environmental enrichment resulted in a significant reduction or complete remission of bumblefoot lesions in captive Magellanic penguins (Reisfeld et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, most penguins spend less than 20% of their time on land in the wild; therefore, it has been suggested that increased time spent defending territory on land in captivity predisposes penguins to bumblefoot [Ellis-Joseph, 1990;Reidarson et al, 1999;Williams, 1995]. Increasing feeding opportunities and environmental enrichment in the water have resulted in reduced incidences of bumblefoot in penguins at other facilities, further supporting the importance of swimming activity in preventing the formation of plantar lesions [Reidarson et al, 1999;Reisfeld et al, 2010]. Results also indicated in this study that the affected male population with plantar lesions did stand significantly more than swim; therefore, limited activity may contribute to the development of plantar lesions in male penguins, but not necessarily the female penguins.…”
Section: Discussionmentioning
confidence: 99%
“…Because standing activity was observed significantly more than swimming activity in the affected penguin population, it is strongly recommended to encourage swimming in aquarium-maintained penguins with environmental enrichment. In a recent study, environmental enrichment, including colored balls, rings, bubbles, and frozen fish, were used to increase swimming for one extra hour a day which resulted in a significant reduction of bumblefoot lesions when compared with penguins that did not interact with the enrichment [Reisfeld et al, 2010]. Feeding penguins in the water from the shore rather than on land has also been suggested as a method of increasing swimming behavior and reducing the incidences of lesions in captivity [Reidarson et al, 1999].…”
Section: Discussionmentioning
confidence: 99%